Incorporation of cobalt ions into magnetoelectric gallium ferrite epitaxial films: tuning of conductivity and magnetization1. Issue 43 (14th May 2015) - Oh, S. H.; Shin, R. H.; Lefèvre, C.; Thomasson, A.; Roulland, F.; Shin, Y.; Kim, D.-H.; Kim, J.-Y.; Demchenko, A.; Leuvrey, C.; Mény, C.; Jo, W.; et al.
<x xml:space="preserve">Abstract</x> Doping Ga0.6Fe1.4O3 thin films with magnetic Co2+ ions leads to a strong reduction in the charge conduction and does not lead to any modification of the ferrimagnetic transition. This is absolutely comparable to that observed with Mg-doping.